PENGARUH SUMBER BAHAN ORGANIK TERHADAP KANDUNGAN KIMIA MIKROORGANISME LOKAL (MOL) - Julianus Jeksen (Fakultas Pertanian, Universitas Nusa Nipa, 2022)
Local Microorganisms (MOL) are microorganisms that are used as starters in the manufacture of solid organic fertilizers and liquid fertilizers. To determine the nutrient content in MOL, an analysis was carried out at the Soil Chemistry Laboratory, Faculty of Agriculture, Nusa Cendana University, Kupang. The purpose of the study was to determine the content of macro nutrients (N, P, K and C-Organic), and to determine the content of micro nutrients (Mn, Fe, Cu, Zn) as well as the pH and C/N Ratio of the results of the manufacture of Local Microorganisms. The study was conducted in the experimental garden of Nusa Nipa University for ± 4 months from February to July. The macro nutrient content of MOL from the results of the study was 16.95% C-Organic, 2.06% N, 0.29% P, 1.85% K, based on kerinyuh; 8.91% C-Organic, 2.79% N, 0.34% P, 1.32% K, based on gamal leaves; 0.23% C-Organic, 1.23% N, 0.18% P, 0.80% K, based on lamtoro; 3.44% C-Organic, 1.53% N, 0.20% P, 1.29% K, based on mustard green waste; 1.11% C-Organic, 2.78% N, 0.33% P, 1.17% K, based on cow rumen and the content of MOL micronutrients from the research results were 4.01% Mn, 108.78ppm Fe, 0.03ppm Cu, 1.73ppm Zn, pH 4.07 and C/N Ratio 8.23 ​​based on kerinyuh; 3.12% Mn, 100.91 ppm Fe, 0.03ppm Cu, 1.71ppm Zn, pH 4.89 and C/N Ratio 3.20 based on gamal leaves; 3.01% Mn, 101.11ppm Fe, 0.03ppm Cu, 1.70ppm Zn, pH 5.10 and C/N Ratio 0.18 based on lamtoro; 3.38% Mn, 104.5ppm Fe, 0.02ppm Cu, 1.65ppm Zn, pH 4.89 and C/N Ratio 2.25 based on mustard green waste. 3.70% Mn, 106.82ppm Fe, 0.03ppm Cu, 1.69ppm Zn, pH 4.98 and C/N Ratio 0.40 based on cow rumen.